2018
DOI: 10.1111/ijcs.12445
|View full text |Cite
|
Sign up to set email alerts
|

Mental accounting and behavioural hierarchy: Understanding consumer budgeting behaviour

Abstract: Budgeting is an important step in consumer finance. Budgeting behaviour is considered a desirable financial behaviour to indicate consumer financial capability. However, systematic research on budgeting behaviour with a large scale national sample is limited. The purpose of this study was to address this research gap and examine characteristics of budgeting behaviour from the perspective of a behavioural hierarchy, which is related to mental accounting. The assumption holds that consumer financial behaviours m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 30 publications
2
26
0
4
Order By: Relevance
“…Empirical research on the association between present bias and money management is limited. Some research shows that consumer budgeting and planning behaviors are associated with consumer resource levels, in which consumers with limited resources are more likely to perform budgeting behavior and less likely to engage in planning behavior (Xiao & O'Neill, , ). In addition, research has found normative financial management behaviors including calculating retirement needs are positively related to financial resilience when consumers face financial distress (Bhargava, Palmer, Chatterjee, & Stebbins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research on the association between present bias and money management is limited. Some research shows that consumer budgeting and planning behaviors are associated with consumer resource levels, in which consumers with limited resources are more likely to perform budgeting behavior and less likely to engage in planning behavior (Xiao & O'Neill, , ). In addition, research has found normative financial management behaviors including calculating retirement needs are positively related to financial resilience when consumers face financial distress (Bhargava, Palmer, Chatterjee, & Stebbins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Asaad (2015) and Allgood and Walstad (2016), we found that not only knowing more about financial matters is linked with recommended behaviors, but financial self‐efficacy as well. The results of Table 5 show that compared to born Canadians: Immigrants are less likely to plan for their retirement; Established immigrants are more likely to plan for their retirement than recent immigrants (significant at p value <.01); Recent immigrants are more likely to have a household budget perhaps due to limited economic resources (Xiao and O'Neill, 2018) and are less likely to check their credit reports. …”
Section: Resultsmentioning
confidence: 99%
“…Financial behaviors can either increase or impede the enhancement of financial well‐being. Individuals' financial well‐being 5 is related to incorporating a “skillful combination of financial knowledge and behaviour” (Xiao and O'Neill, 2018, 449). We argue that, after controlling for the effects of financial knowledge, immigrants' financial behaviors differ from those of born citizens and ultimately affect their financial well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Some research shows that consumer budgeting and planning behaviors are associated with consumer resource levels, in which consumers with limited resources are more likely to perform budgeting behavior and less likely to engage in planning behavior (Xiao & O'Neill, 2018a, 2018b. In addition, research has found normative financial management behaviors including calculating retirement needs are positively related to financial resilience when consumers face financial distress (Bhargava, Palmer, Chatterjee, & Stebbins, 2018).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%